2017
DOI: 10.1002/tea.21385
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to dialogic discourse in SSI teaching: The effects of an argumentation‐based workshop, teaching practicum, and induction on a preservice science teacher

Abstract: Teaching socioscientific issues (SSI) necessitates dialogic discourse activities. However, a majority of science teachers prefer monologic discourse in SSI contexts. In addition, some of these teachers are resistant to change (from monologic to dialogic discourse) despite certain professional development attempts. The purpose of the present single-case study was to investigate the nature of this resistance in a preservice science teacher (PST) (Duygu). We longitudinally followed preservice teachers through 1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 44 publications
0
46
0
4
Order By: Relevance
“…This may be due to the fact that the education received at the university does not have enough quality to develop critical thinking skills of the PSTs because they do not have enough experience to develop their critical thinking skills during monological process in education that is usually based on expository teaching (Kilinc, Demiral & Kartal, 2017). The importance of methods that provide opportunity for dialogic communication in the development of critical thinking skills have determined that argumentation (Demiral, 2014;Demiral & Çepni, 2018), inquiry-based activities (Belluigi & Cundill, 2017;Ernst & Monroe, 2004) that they have conducted within the context of environmental education develop critical thinking skills.…”
Section: Teacher Training Program and Critical Thinkingmentioning
confidence: 99%
“…This may be due to the fact that the education received at the university does not have enough quality to develop critical thinking skills of the PSTs because they do not have enough experience to develop their critical thinking skills during monological process in education that is usually based on expository teaching (Kilinc, Demiral & Kartal, 2017). The importance of methods that provide opportunity for dialogic communication in the development of critical thinking skills have determined that argumentation (Demiral, 2014;Demiral & Çepni, 2018), inquiry-based activities (Belluigi & Cundill, 2017;Ernst & Monroe, 2004) that they have conducted within the context of environmental education develop critical thinking skills.…”
Section: Teacher Training Program and Critical Thinkingmentioning
confidence: 99%
“…The teaching of argumentation, in which students need to build arguments by considering evidence and counter evidence, using appropriate reasoning, and evaluating alternative standpoints, has become increasingly prevalent and also an essential goal for science education (Duschl, Schweingruber, & Shouse, ; Moon, Stanford, Cole, & Towns, ; Osborne et al, ). It has been reported that argumentation is rarely found in the science discourse of most students, because regular classroom discourse typically follows a pattern in which the teacher initiates discussion by using a question with a known answer, the students respond to the question, and then the teacher evaluates the students' responses (Driver, Newton, & Osborne, ; Kilinc, Demiral, & Kartal, ; Lemke, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a kind of cooperation between undergraduates, peer feedback motivates undergraduates to make the feasibility study report through discussion and negotiation. It sharpens undergraduates' oral and written communication, writing, critical thinking and self-learning skills (Kilinc et al, 2017;Wu, 2012).…”
Section: Peer Feedback and Teacher Feedbackmentioning
confidence: 99%